The Effect of Courageous Learning on the Clinical Practice Ability of Midwifery Students During the Covid-19 Pandemic - Dewi Nurlaela Sari (Jurnal Medika : Karya Ilmiah Kesehatan, 2021)
Online learning is one of the learning efforts developed during the COVID-19 pandemic. Online learning is felt to be effectiveat all levels of education. However, this is not the case with vocational education, especially in the health sector. Onlinelearning can also have an impact on the competencies that students must achieve because there is no direct interactionbetween students, lecturers, props/phantoms and place settings that can support the implementation of clinical skills. Thepurpose of this study was to determine the effect of online learning on the Practice Ability of Midwifery Students during theCovid-19 Pandemic . The type of research method used is pre eksperimental . Sampling was done by using purposivesampling totaling 30 respondents . The instrument used to measure students ' clinical practice skills is a checklist forchildbirth assistance, the statistical test carried out is through the normality test stages using Shapiro Wilk with the resultsof the data not being normally distributed so that an analysis test is carried out using the Wilcoxon Signed Rank Test. Theresults of the study obtained a p-value of 0.000 < from the alpha value (0.05). It can be concluded that there is asignificant influence between students ' ability to perform midwifery care related to the impact of online learning duringmidwifery clinical practice . It is hoped that the results of this study can be used as the basis for policies regarding thedevelopment of online learning methods that can support the achievement of competencies, especially clinical skills.